2016
DOI: 10.1136/heartjnl-2015-308821
|View full text |Cite
|
Sign up to set email alerts
|

ECG features and proarrhythmic potentials of therapeutic hypothermia

Abstract: J waves were recorded in about 40% of the patients who received TH. They were most frequently observed in the inferior limb leads or lateral precordial leads. Life-threatening VF occurred only rarely (1.7%) during TH and were mainly observed in patients with primary arrhythmic disorder. Although a causal relationship between TH-induced J waves and VF remains unknown, administering TH to this potentially susceptible, high-risk population may require careful attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…The incidence of ventricular arrhythmia in our study (6% VF, 13%VT) is seemingly higher than the one recently reported by Lee et al [12] with only 1.7% of patients with VF. However, we report the occurrence of arrhythmia the first three days after OHCA in a cohort including a majority of patients resuscitated from a shockable rhythm.…”
Section: Osborn Waves and Arrhythmogenecitycontrasting
confidence: 82%
See 2 more Smart Citations
“…The incidence of ventricular arrhythmia in our study (6% VF, 13%VT) is seemingly higher than the one recently reported by Lee et al [12] with only 1.7% of patients with VF. However, we report the occurrence of arrhythmia the first three days after OHCA in a cohort including a majority of patients resuscitated from a shockable rhythm.…”
Section: Osborn Waves and Arrhythmogenecitycontrasting
confidence: 82%
“…The relatively high overall OW incidence on admission (16%) may be attributable to a low admission temperature of around 35°C [13]. Recent smaller studies have shown a OW prevalence in OHCA-patients treated with TTM at 33°C ranging from 40-60% [12,27,28], likewise, OW were more prevalent in patients with STEMI vs. non-STEMI (38.6% vs. 15.2%) [29]. These findings correlate with our data showing that patients after OHCA presenting with OW have more invasive procedures performed (PCI 49% vs. 39%, p=0.01) possibly explained by higher degree of coronary ischemia.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In accidental hypothermia patients (29.4°C-33.5°C) with J-waves, only one developed ventricular tachycardia (VT) (75) and J-waves does not predict survival chance (39). A multi-centre study from South Korea observed J-waves in 41% of therapeutic hypothermia patients, while VF only occurred in 1.7% (80), which concurs with other studies (81). J-waves are more common in hypothermic STEMI (38.6%) than non-STEMI (15.2%) patients (45).…”
Section: Vectorcardiographic Recordings Show the Three-dimensional DImentioning
confidence: 99%
“…In urban accidental hypothermia, underlying conditions and substance abuse can be as important predisposing factors for cardiac arrest as core temperature (61). In therapeutic hypothermia, ventricular ectopic activity is increased (97) and non-sustained VT can occur frequently (34), but sustained ventricular arrhythmias are uncommon in most (34,35,45,62,80) but not all studies. Mirzoyev found polymorphic VT in 11.7% of therapeutic hypothermia patients.…”
Section: Clinical Studiesmentioning
confidence: 99%